The Implementation of Curriculum-Integrated Reading Corners to Enhance Reading Interest among Grade 5 Students at MIS Humayroh - Sagala, Risa Alvina; Napitupulu, Dedi Sahputra; Sitorus, M.Walimsyah (FKIP - Universitas Riau, 2025)
This study aims to examine the effectiveness of reading corners integrated with curriculum-based learning materials in increasing elementary school students’ interest in reading. Reading interest at the elementary level is a crucial component in building a strong foundation in literacy. One approach to enhancing reading motivation is through engaging and relevant instructional methods, such as the use of reading corners integrated with subject content. This research employed a descriptive method, with data collected through observations, student questionnaires, and teacher interviews. The results showed that 86.7% of students reported increased enthusiasm for reading after the implementation of the reading corner. Students also became more active in seeking information related to lesson themes. The inclusion of curriculum-relevant texts in the reading corner supported more contextualized and meaningful learning experiences. Therefore, integrating reading corners with instructional materials proved effective in fostering students’ reading interest. It is recommended that schools enhance the variety and relevance of reading materials to maximize the impact of reading corners in supporting elementary education.